An Application of Spatial Equilibrium Analysis to the Paddy Postharvest System in Tanjong Karang, Peninsular Malaysia - Yahya, Salleh (1988)
Paddy postharvest losses in Malaysia range between 10 percent to 37 percent. These losses occur during manual handling in harvesting of paddy, threshing, drying, storing and milling. The major cause of these losses is attributed to improper handling methods and inadequate handling facilities. In addition, the industry also faces problems of deterioration in paddy quality, low quality rice and high transportation cost. In the present postharvest system, paddy is handled in gunny bags. Besides being costly, this type of handling method also causes delays in processing the paddy resulting in discoloration of paddy and rice , development of moulds and fungus causing loss of value . A spatial equilibrium model was used to analyse the existing paddy postharvest system in Tanjong Karang as well as to determine measures to improve the industry. The model is basically a linear programming model with the objective function of maximizing net industry revenue. The model constraints consist of twenty nine set of equations relating to paddy and rice flows, capacity, queuing, handling, pricing, supply and demand. The short-run economic situation is simulated in the model to find the optimal solution. Results obtained from the model show the optimal flows of paddy and rice from production areas to procurement centres, mills and final markets, together with the costs involved in each of the activities.